Analisis Bioekonomi Ikan Cakalang dalam Upaya Pengelolaan Sumberdaya Perikanan Berkelanjutan - Rasdam Rasdam; Mustasim Mustasim (Jurnal Airaha, 2019)
One of the potential of marine products Sorong big enough to be developed in fisheries is Skipjack fish. This study aims to determine the production of maximum sustainable yields (MSY), the level of economic benefits (MEY) and the utilization rate Skipjack fish. The method used stratified random sampling and that became the sample is obtained from the Skipjack fish catches landed in Sorong. The results were obtained MSY amounted to 5,006,321.52 tons / year to an effort of 40 vessels / year while MEY to fish Skipjack 4,999,399.970 tons / year and Effort Maximum Economic Yield (EMEY) 38 vessels / year with a utilization rate has exceeded the amount haul allowed (JTB) that is 80% of the Total Allowable Catch (TAC) which is equal to 106.88%. The result of the calculation of a long relationship forked and weight of Skipjack fish obtained equation W = 0.1931 L 2.4447. Value b = 2.4447, (b less than 3), the pattern of growth Skipjack fish landed in Sorong Regency is Allometric negative. Conditions Skipjack been over exploited fisheries, the management system in accordance with the fisheries Skipjack in Sorong based on the biological aspects include: (1). Setting the fishing season (2). The closure of fishing grounds in certain seasons. (3). Reduction arrest quotas. (4) .Control fishing effort.